Medidor de consumo de energia elétrica com acesso local e remoto usando plataforma ESP8266 - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The consumption of electric power and the control of this consumption is a very important issue in the current Brazilian context, since the values charged and taxed on this energy are some of the highest in the global level, where a third of the consumption consists of residential consumers. The scenario becomes even more critical when one notices the absence and the difficult (or nonexistent) access to mechanisms of auditing and control of consumption by the customer, which contributes negatively to the creation of a culture of economy and good use of electric energy. As a possible answer to these questions, this work intends to propose the architecture of an electric meter prototype. The initiative aims to research, evaluate and propose a low cost and affordable system from the economic and practical points of view for residential customers. This is expected to motivate the research and development of meters that do not demand complexity or cost above the consumption reality of residential customers. The system to be presented consists of a sine-wave (alternating current) voltage and current meter, whose core is a NodeMCU Lolin development module (equipped with an ESP8266-12E microcontroller), taking advantage of native resources to the Arduino platform. The features of the prototype are the measurements already mentioned, real-time active power calculation, energy consumption storage, recording of all this data in a datalogger and also transmission of this data with a Message Queue protocol Telemetry Transport (MQTT) to be retrieved by WEB applications or cell phones with Internet connection.
Keywords: Engenharia elétrica; Energia elétrica; Consumo de energia elétrica; Electrical engineering; Electricity; Electric power consumption; CNPQ::ENGENHARIAS